Practical Guide to SAP Profit Center Accounting - Pringle, John (Espresso Tutorials GmbH, 2016)
This book offers a comprehensive introduction to SAP ERP Profit Center Accounting (PCA) for both classic general ledger (GL) and the new GL. Get the tools you need to set profitability targets for business (planning) and then compare actual results against those targets to improve overall profitability. Solidify your understanding of the difference between PCA and SAP Controlling Profitability Analysis (CO-PA) views. Gain in-depth knowledge of the concepts, objects, and functionality available in PCA in SAP ERP, including the relevant master data set-up, actual data flows, planning scenarios, and reporting options. Clarify the differences between PCA and CO-PA and understand when it is best to use each. Dive into profit center transfer pricing and obtain detailed configuration and set-up steps required for activation. By using practical examples, tips, and screenshots, the author brings readers up to speed on SAP Profit Center Accounting.- Fundamentals of SAP Profit Center Accounting (PCA) - Concepts, master data, actual data flow, and planning basics - Differences between PCA in classic and new GL - Reporting for Profit Center Accounting (PCA)